Series VII: Endangered Gender - Elizondo González, Jose Fabián (2020)
This series of poems attempts to address a myriad of psychological issues suffered by LGBTQI+ people today. These poems pinpoint those misconceptions and traumas about gender identity and sexuality that later reflect in insecurities, internalized oppression, and even death